Phenotypic and transcriptomic characterization of canine myeloid-derived suppressor cells - Goulart, Michelle R. (Sci Rep, 2019)
Myeloid-derived suppressor cells (MDSCs) are key players in immune evasion, tumor progression and metastasis. MDSCs accumulate under various pathological states and fall into two functionally and phenotypically distinct subsets that have been identified in humans and mice: polymorphonuclear (PMN)-MDSCs and monocytic (M)-MDSCs. As dogs are an excellent model for human tumor development and progression, we set out to identify PMN-MDSCs and M-MDSCs in clinical canine oncology patients. Canine hypodense MHC class II(−)CD5(−)CD21(−)CD11b(+) cells can be subdivided into polymorphonuclear (CADO48A(+)CD14(−)) and monocytic (CADO48A(−)CD14(+)) MDSC subsets. The transcriptomic signatures of PMN-MDSCs and M-MDSCs are distinct, and moreover reveal a statistically significant similarity between canine and previously published human PMN-MDSC gene expression patterns. As in humans, peripheral blood frequencies of canine PMN-MDSCs and M-MDSCs are significantly higher in dogs with cancer compared to healthy control dogs (PMN-MDSCs: p < 0.001; M-MDSCs: p < 0.01). By leveraging the power of evolution, we also identified additional conserved genes in PMN-MDSCs of multiple species that may play a role in MDSC function. Our findings therefore validate the dog as a model for studying MDSCs in the context of cancer.